The Effect of High Stimulant Concentrationon the Yield and Dry Rubber Content of High Metabolic Clone Rrim 911 in Low-Tapping Frequency Practice - Atminingsih Atminingsih; Radite Tistama; Junaidi Junaidi; Irwan Saban (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2019)
The low-frequency tapping (d4) offers an opportunity to exploit the latex through the increments of stimulant concentration and application frequency. This study compared the yield and dry rubber content (DRC) from three different stimulant compounds i.e. etephon 5.0% (ET), polyethylene glycol 3.0% + palmitic acid 0.2% + etephon 5.0% (EN), and polyethylene glycol 3.0% + palmitic acid 0.2% (NS). A field trial was carried out at Tanah Besih Estate, North Sumatera using 17 years of age RRIM 911 clone based on Complete Block Design. The data was collected from May 2017 to February 2018. The result suggested that the ET was the strongest compound that able to generate higher yield (56.37 gt-1t-1) than EN and NS (56.37 gt-1t-1 and 34.00 gt-1t-1 respectively). Nevertheless, the high concentration tended to have a slightly lower DRC. When etephon was combined with other compounds, it lowered the effect on the yield. All treatments showed that the first and second tapping after stimulant application generated highest yield. The yield in mature leaves had lowed yield in ET and EN treatments, while NS showed a significant increase. Our result suggested that the application of high concentration of etephon was very effective to obtain the yield.